Trade exposure of Western Europe to China and Eastern Europe: A spatial econometric analysis of the effects on regional manufacturing employment from 1991-2011 - Harald Badinger; Wolf Heinrich Reuter (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2017)
This study analyzes the effects of increased trade with China and Eastern Europe on manufacturing employment in 1,146 NUTS-3 regions of 17 Western European countries from 1991 to 2011. Building on Autor et al. (2013) we aim at identifying the causal effects of an increase in import and export exposure on regional manufacturing employment, thereby, explicitly accounting for labor and product market spillovers. Overall, our results support previous findings of a negative effect of increased import exposure from China for our sample of Western European countries, whereas spatial spillover effects turn out to be positive, slightly mitigating the quantitative impact without changing results quantitatively. Moreover, our cross-country study highlights the pronounced heterogeneity of the estimated effects of trade exposure on manufacturing employment across countries with respect to the trade balance.
Keywords: F16; J31; R11; 330; International Trade; Globalization; Western Europe; China; Eastern Europe; Employment